Masalah Kejiwaan sebagai Inspirasi Karya Seni Lukis Surealis - Putri, Rika; Asa, Ferdian Ondira (Lembaga Yasin AlSys, 2025)
The purpose of the final work is to provide education about several types of mental health problems that originate from social factors of surrealist paintings. The author took data through observations of people with mental health problems around the author, and developed it into an idea using I Bandem method as an art consortium the has five stages, from the preparation stage, the elaboration stage, the synthesis stage, the realization stage, the concept and the completion stage. Based on observation and development of ideas, the author can visualize ten surrealist paintings, with various size ranging from 100cm x 100cm to 100cm x 130cm with the title of the :“Nolep”, “Lebay”, “Bodoh”,“Jangan”, “Pembohong”, “Caper”, “Moodyan”, “Istirahat”, “Liburan”, “Pikun”.